Two new species of soil mites (Acari, Oribatida, Oppiidae and Machuellidae) from Turkey - Baran, Şule; Ayyildiz, Nusret (Zootaxa, 2007)
Two new species of soil mites (Acari: Oribatida), Machuella turcica sp. nov. (Machuellidae) and Oxyoppia (Dzarogneta) ilicaensis sp. nov. (Oppiidae) are described from Turkey. They were collected from moss on rocks and litter under oak trees respectively. A key to the known species of the genus Machuella Hammer, 1961 is provided.